Intuitive eating behaviour and its association with body mass index and weight control behaviour among young chinese adults in Universiti Tunku Abdul Rahman - Oon, Choy Li (2024)
Prevalence of obesity in Malaysia had increase over the years thus, few related journals were published on this topic. However, there were limited studies on intuitive eating concept that has been associated with weight loss. Therefore, this study determined intuitive eating behaviour (IEB) as well as its association with Body Mass Index (BMI) and weight control behaviours (WCB) among young Chinese adults in Universiti Tunku Abdul Rahman (UTAR). A cross-sectional, validated questionnaire was conducted on 436 university students through convenience sampling selection. The questionnaire used consists of BMI, Intuitive Eating Scale-2 questions and weight control behaviours questions. Data collected was analysed using SPSS version 27.0 then reported in descriptive and inferential statistics. Independent samples T test was used to determine difference among genders in terms of intuitive eating score and subscale scores. Chi-square test was used to assess association between gender and IEB, IEB and BMI also IEB and WCB. The overall mean intuitive eating score was 3.45 ± 0.353 while highest score can be found in Reliance in Hunger and Satiety Cues subscale. Men scored higher than women in overall mean intuitive eating score and all subscale scores. However, women scored higher in intuitive eating behaviour than men by a 10% difference. Higher percentage of intuitive eating behaviour were found in underweight and normal weight individuals. In conclusion, UTAR students are not considered as intuitive eaters and there was no significant difference among genders in terms of scores (all p-values>0.05). A significant association was found between gender and IEB (p-value=0.006). No significant association found between IEB and BMI (p-value=0.297) as well as IEB and WCB (p-value=0.427). Findings gathered may be used to implement assorted programs in bringing up awareness concerning on how intuitive eating concept helps in weight loss in hopes of improving quality of life among university students.